Evaluation of microbial species inactivation and purification of pond sewage by a custom‐built air surface discharge plasma. Issue 6 (4th April 2021) - Liu, Zhijie; Xu, Dehui; Pang, Bolun; Wang, Sitao; Wang, Shuai; Gao, Yuting; Peng, Sansan; Chen, Hailan; Kong, Michael G.
Abstract: The presence of the hazardous microbial species in pond sewage is a serious threat to the aquatic environment and human health, and an effective purification method is urgently needed. Here, we reported the evaluation and purification effect of sewage by a custom‐built air surface discharge plasma. Results show that the most sensitive bacterial flora mainly includes Cyanobium, Candidatus, and Proteobacteria, based on inactivation map by the DNA sequence. The inactivation of microbial species by plasma treatment would reach beyond 5‐log reduction and the water turbidity would be effectively improved. Identification of the significance of reactive oxygen and nitrogen species with scavengers indicates that the purification effect is closely linked to the key agents ONOO − and H2 O2 . This study would contribute to an in‐depth insight into decontamination and provide a potential alternative for sewage purification. Abstract : The presence of the hazardous microbial species in pond sewage is a serious threat to the aquatic environment and human health, and effective purification method is urgent needed. Here, we reported the evaluation and purification effect of pond sewage by a custom‐built air surface discharge plasma. Our results would contribute to in‐depth insight into the decontamination of municipal sewage and provide a potential alternative to conventional methods for sewage purification.